Jacob Brown papers - Brown, Jacob, 1775-1828.
Two official letterbooks, chiefly 1814-1828, containing copies of incoming and outgoing correspondence, memoranda, accounts, and reports, relating to the military career and activities of Major-General Brown, especially his participation in various battles of the War of 1812 around Niagara, Fort Erie, and Lake Ontario; and as commander of the Division of the North, with headquarters at Brownville, N.Y. Includes material on general military matters, troop movements, army reorganization, establishment of forts and other military construction, and relations with the Indians, namely a "Memorandum of the Tribes of Indians in the North-West...." with various statistics on the tribes and their ways of life. A third volume entitled "Memorandum of occurrences and some important facts attending the Campaign on the Niagara in 1814" contains memoranda and copies of correspondence relating to the Battle of Lundy's Lane in which Brown figured prominently. Correspondents include John Armstrong, James Barbour, John C. Calhoun, Isaac Chauncey, De Witt Clinton, William Harris Crawford, Alexander James Dallas, Edmund Pendleton Gaines, George Graham, George Izard, Andrew Jackson, Alexander Macomb, James Monroe, Daniel Parker, and Winfield Scott.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Army officer.
Collection material in English.
Keywords: Armstrong, John, -- 1758-1843 -- Correspondence; Barbour, James, -- 1775-1842 -- Correspondence; Calhoun, John C. -- 1782-1850 -- Correspondence; Chauncey, Isaac, -- 1772-1840 -- Correspondence; Clinton, DeWitt, -- 1769-1828 -- Correspondence; Crawford, William Harris, -- 1772-1834 -- Correspondence; Dallas, Alexander James, -- 1759-1817 -- Correspondence; Gaines, Edmund Pendleton, -- 1777-1849 -- Correspondence; Graham, George, -- 1770-1830 -- Correspondence; Izard, George, -- 1777-1828 -- Correspondence; Jackson, Andrew, -- 1767-1845 -- Correspondence; Macomb, Alexander, -- 1782-1841 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Parker, Daniel, -- 1782-1846 -- Correspondence; Scott, Winfield, -- 1786-1866 -- Correspondence; United States. -- Army. -- Division of the North; Fortification -- Ontario; Fortification -- New York (State); Indians of North America -- Northwest, Old; Lundy's Lane, Battle of, Ont., 1814.; Fort Erie (Ont.) -- History; New York (State) -- History -- War of 1812.; Niagara Falls (N.Y.) -- History; Northwest, Old -- History -- War of 1812.; Ontario, Lake, Region (N.Y. and Ont.) -- History; United States -- History -- War of 1812 -- Campaigns; Army officers